Ultrastructural Assessment of the Integrity of the enteric Mucosa of Commercial Turkeys Vaccinated against Coccidiosis - MRFB,Martins (2016)
ABSTRACT The objective of this study was evaluated the villus integrity of commercial turkeys submitted to coccidiosis prevention methods and challenged with Eimeria field oocysts, using scanning electron microscopy. Sixty BUT 9 female commercial turkeys were distributed in a completely randomized block design split with two treatments: T1- control diet without vaccinations against coccidiosis and anticoccidial drug, and T2- vaccinated against coccidiosis (commercial vaccine). On d 21 of life, all birds of all treatments were challenged with a mixed-species containing E. meleagrimitis and E. galopavonis, via crop intubation with 1 mL of ~20,000 sporulated oocysts/bird. The size of the inoculum was determined in previous experiments. At 27 and 70 days of age, five birds per treatment were randomly removed to evaluate the intestinal integrity. Duodenum, jejunum and ileum segments were collected and processed according to routine scanning electron microscope. The enteric mucosa integrity of the commercial turkeys subjected to coccidiosis vaccination was reduced when compared to the birds of the control treatment. There was no difference in the performance results, therefore these results cannot be attributed to the vaccination as well as to the ineffectiveness against the challenge that was administered.